Literatur Review: Peran Job Analysis dan Kepuasan Kerja Terhadap Kinerja Karyawan - Addawiyah, Makhriffah Robbiah; Permatasari, Wahyuning Tyas; Aprilia, Jihan; Trisnawati, Vania; Merdianty, Netty (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Carrying out job analysis can identify job requirements and ensure personnel alignment. Job analysis really helps improve employee performance and their job satisfaction. This research aims to provide an overall overview of the available literature on the role of job analysis and job satisfaction on employee performance through various sources and produce a summary and results based on the findings. The review was conducted by reading and analyzing 30 peer-reviewed journal articles. This study will summarize journal articles in tables; the first table explains the title, author, and year of publication; The second table describes the model, subjectively discussed, findings, and proposals. The results of this study have been documented; Employee performance is directly influenced by the relationship between workload, competency, and job analysis, which shows how important it is to align job demands with employee abilities. Job satisfaction directly affects employee performance, which shows how important it is for organizations to increase employee satisfaction.